OWE-008 Patients' perception of faecal calprotectin testing in inflammatory bowel disease: a multi-centre prospective survey. (8th June 2018) - Kalla, Rahul; Boyapati, Ray; Vatn, Simen; Hijos, Gonzalo; Crooks, Benjamin; Moore, G; Hall, Veronica; Tatersall, Suzanne; Lipscomb, George; Gomollon, Fernando; Jahnsen, Jorgen; Singh, Salil
Abstract : Introduction: Faecal Calprotectin is an established biomarker in the investigation and management of Inflammatory Bowel Disease (IBD). Despite its success, there appears to be practical issues with FC testing in clinical practice, including sample collection, sample delivery and processing delays. There are no studies exploring patients' perception of faecal testing in IBD. We investigate patients' perception of FC testing in clinical practice across centres in UK, Europe and Australia. Methods: A prospective patient survey was undertaken in an IBD unit in England from 12/2016 to 2/2017 and extended to 3 centres (Spain, Australia and Norway) from 07/2017 until 11/2017. Patients were asked to complete a 9-point based questionnaire in clinic which included diagnosis, patient demographics, previous FC testing, FC sample collection difficulty rating score (0–4) and preference to alternative methods of disease monitoring including blood tests and endoscopy. Predictors of FC testing difficulty were derived using multivariable logistic regression analysis. Continuous variables were categorised using integer cut points guided by the ROC curves and their relationship to the FC rating score. Results: A total of 585 patients with IBD completed the survey. There were 306 males (52%) with a median age of 43 years (IQR: 31–54). A total of 299, 279, and 7 patients had a diagnosis of CD, UC, IBDU respectively. Median disease duration of the entire cohort was 36 months (IQR 22–66 months). There were 446 patients (76%) who had prior FC testing experience. Of these, 37% (n=165) rated FC testing either moderately difficult (score 2), difficult (score 3) or very difficult (score 4). The reasons included 'dropping FC sample' (n=14; 9%), 'sample collection' (n=106; 67%) or 'both' (n=39; 25%). In these patients, 80%(n=130) patients would rather have a blood test over faecal testing. Categorical multivariable regression analysis was performed to identify factors that predict a high FC difficulty rating score. Using age, gender, disease duration, disease subtype, use of collection kits and geographical location as covariates, age <49 years (OR 2.9, CI: 1.9–4.7), disease duration <35 months (OR 1.4, CI:0.9–2.1) and testing in the UK centre (OR 1.9, CI:1.2–3.1) were predictors of a high difficulty rating score. Conclusions: Our study is the first to explore patients' perception of FC testing as a routine biomarker in IBD across Europe and Australia. A significant 37% find FC testing challenging, in particular those aged <49 years with disease duration <35 months. Further qualitative studies understanding and addressing these practical issues may aid higher FC uptake in clinic.